Population awareness of cardiovascular disease risk factors and health care seeking behavior in the UAE - Mahra Nooruddin Kazim; Tagried Hamdan AbouMoussa; Fatima Ahmed AL-Hammadi; Asma Al Ali; Fariba Mohammad Abedini; Fatma Sayed Mahdi Ahmad; Maryam Yousef Bazdar; Frederick Robert Carrick; Mahera Abdulrahman (Elsevier, 2021)
Objectives: We aimed to determine the awareness, knowledge, and attitude of people residing in Dubai, United Arab Emirates, regarding cardiovascular disease (CVD) risk factors. Our aim was to further identify prospects to increase awareness of modifiable CVD risk factors and influence behavior. Methods: This observational study was conducted in Dubai: a global city in the United Arab Emirates. Participants were selected using simple randomization approach in primary health care centers, and a questionnaire was implemented based on literature review. Results: Out of 1020 individuals approached, 738 agreed to participate in the study (response rate of 72%).The majority of participants surveyed had good knowledge and attitude toward CVD (528, 71.5% and 445, 60% respectively); yet, poor/fair practice related to CVD risk factors (553, 75%). Predictive Margins of Knowledge Scores were significant for age (p<.01), academic level (p<.0001), and nationality (p<.0001) (Table 5). Participants aging 40-49, non-UAE subjects, and university/Postgraduate academic level scored better on the knowledge. Demographics predictor for practice score was highly significant for age (p=.0001) and BMI (p=.0001). Those aging ≥50 and obese participants scored higher on practice toward CVD risk factors. Knowledge score was significant predictor of practice and attitude toward CVD risk factors (p=.0001, p<.0001) Conclusions: Although more than half of the current study participants had high knowledge and attitude toward CVD, their behaviors were not satisfactory. It is necessary to establish more effective educational interventions intended to promote positive health behaviors. Public health providers need to explain to the public that knowledge and proper actions regarding the reduction of risk factors are associated with reduced CVD and mortality.